Capsaicin functions as a selective degrader of STAT3 to enhance host resistance to viral infection - Zhang Mei-qi; Jia Xin; Cheng Cui-qin; Wang Yu-xi; Li Yi-ying; Kong Ling-dong; Li Qi-qi; Xie Fang; Yu Yan-li; He Yu-ting; Dong Qiu-tong; Jia Zhan-hong; et al. (Acta Pharmacologica Sinica, 2023)
Although STAT3 has been reported as a negative regulator of type I interferon (IFN) signaling, the effects of pharmacologically inhibiting STAT3 on innate antiviral immunity are not well known. Capsaicin, approved for the treatment of postherpetic neuralgia and diabetic peripheral nerve pain, is an agonist of transient receptor potential vanilloid subtype 1 (TRPV1), with additional recognized potencies in anticancer, anti-inflammatory, and metabolic diseases. We investigated the effects of capsaicin on viral replication and innate antiviral immune response and discovered that capsaicin dose-dependently inhibited the replication of VSV, EMCV, and H1N1. In VSV-infected mice, pretreatment with capsaicin improved the survival rate and suppressed inflammatory responses accompanied by attenuated VSV replication in the liver, lung, and spleen. The inhibition of viral replication by capsaicin was independent of TRPV1 and occurred mainly at postviral entry steps. We further revealed that capsaicin directly bound to STAT3 protein and selectively promoted its lysosomal degradation. As a result, the negative regulation of STAT3 on the type I IFN response was attenuated, and host resistance to viral infection was enhanced. Our results suggest that capsaicin is a promising small-molecule drug candidate, and offer a feasible pharmacological strategy for strengthening host resistance to viral infection.